Pengaruh Lingkungan Kerja dan Motivasi Terhadap Prestasi Kerja Karyawan Pada CV. Jaya Abadi Kota Bima - Devi; Firmansyah Kusumayadi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
: This study aims to determine the work environment partially significant effect on employee performance at CV. Jaya Abadi Bima City, to find out motivation has a partial significant effect on achievement on CV. Jaya Abadi Bima City, to find out the work environment and work motivation have a significant simultaneous effect on employee performance at CV. Jaya Abadi Bima City. Questionnaire research instrument. The scoring technique used in this research questionnaire is a Likert scale. The population in this study were 59 employees at CV. Jaya Abadi Bima City. The sample in this study were 59 permanent employees at CV. Jaya Abadi Bima City with the sampling technique used, namely the saturated sampling technique. Data collection techniques using observation, interviews, questionnaires, documentation. The data analysis technique uses validity test, reliability test, multiple linear regression test, classical assumption test, correlation coefficient test, coefficient of determination, f and t test with the help of SPSS version 21 for windows. The results showed that the work environment did not partially affect employee performance, work motivation partially affected employee performance, work environment and work motivation simultaneously affected employee performance at CV. Jaya Abadi Bima City